Tuning electron transfer through p-phenyleneethynylene molecular wires - Atienza, Carmen; Martín, Nazario; Wielopolski, Mateusz; Haworth, Naomi; Clark, Timothy; Guldi, Dirk Michael (Chemical Communications, 2006)
Weak wire-like behavior - with a damping factor (β) of 0.2 ± 0.05 Å - has been found in a series of C -wire- exTTF systems (i.e., p-phenyleneethynylene): these results contrast with previous observations involving p-phenylenevinylene systems. © The Royal Society of Chemistry 2006.